ICU Mortality in Patients With Coronavirus Disease 2019 Infection: Highlighting Healthcare Disparities in Rural Appalachia. (8th October 2021) - Sharma, Sunil; Badami, Varun; Rojas, Edward; Mittal, Abhinav; Stansbury, Robert; Rana, Bilal; Wilson, Alison; Wen, Sijin
Abstract : OBJECTIVES: To assess 30-day mortality in coronavirus disease 2019 acute respiratory distress syndrome patients transferred from rural Appalachian hospitals. DESIGN: Retrospective case controlled, based on consecutive patients transferred and admitted from rural hospitals to a tertiary-care ICU. The primary outcome was all-cause 30-day mortality. Kaplan-Meier method and log-rank test were used in the survival data analysis. SETTING: Medical ICU, West Virginia University Hospital, Morgantown, WV. PATIENTS: All adult patients admitted to the ICU for coronavirus disease 2019 disease between September 30, 2020, and December 2, 2020. INTERVENTION: Not applicable. MEASUREMENTS AND MAIN RESULTS: Seventy-nine consecutive coronavirus disease 2019 patients were admitted to the ICU during the defined period. Overall mortality of the cohort was 54%. Of the 79 patients, 50 were transferred from critical access hospitals/rural facilities with coronavirus disease 2019–induced acute respiratory distress syndrome. A control group consisted of 39 patients admitted to the ICU with noncoronavirus disease 2019 acute respiratory distress syndrome who were intubated and mechanically ventilated. Thirty-day mortality in patients with coronavirus disease 2019 admitted to the ICU was significantly higher than the control group (68% vs 42%) ( p = 0.034). Mean Sequential Organ Failure Assessment scores were similar in both coronavirus disease 2019 acute respiratory distress syndrome group and controls. Intubation in patients 70 years or older and mechanical ventilation for over 5 days was associated with significantly higher mortality. CONCLUSIONS: Our data on critically ill and mechanically ventilated coronavirus disease 2019 acute respiratory distress syndrome patients transferred from critical access hospitals/rural facilities have increased mortality compared with noncoronavirus disease 2019 acute respiratory distress syndrome controls. These data suggest that lack or delay in access to tertiary care may impact coronavirus disease 2019 outcome in rural areas. Intubated patients 70 years old or more and mechanical ventilation for over 5 days may be a risk factor for increased mortality. These data may help physicians and hospital administrators in rural areas for optimal utilization of limited resources.